Development of body stress analyzer based on physiological signal - Abd. Majid, Nor Aini; Md. Sahar, Nan; Sari, Suhaila; Taujuddin, N. S. A. M.; M.N., Nurliza; Abd Wahab, Mohd Helmy; Ambar, Radzi; Syed Idrus, Syed Zulkarnain (2020)
Ehealth is one of the system that use modern technologies that be apply to the healthcare organization. This system allowed the patient to access the system to monitor their health records and else by using internet as a platform to communicate. Thus, this project is inspired by Ehealth system to making a hardware device with software application that act as monitoring system to the people. For the hardware, the user only need to grasped the two terminal in the device that contains of all the sensor for doing the testing procedure. Thus, all the data that be contain will be sent to the apps via internet of things for storing them. This will helps physical education and health teacher to do observation and record the data obtain from the apps.Besides, this way also will avoiding any incident to be occur towards the students if they carry on the activities in abnormal condition of their body system. The scope for this project is focusing on monitoring students body condition before they starting their outdoor activities in the field. The way for sensing the parameter including pulse sensor, LM35 and Galvanic Skin Response sensor with arduino as a microcontroller to process the input and output signal.